Is Debt Replacing Equity in Regulated Privatized Infrastructure in Developing Countries? - da Silva, Luis Correia (World Bank, Washington, D.C., 2013)
The main purpose of this paper is to describe the evolution of the financing structure of regulated privatized utilities and transport companies. To do so, the authors rely on a sample of 121 utilities distributed over 16 countries, and 23 transport infrastructure operators and 23 transport services operators distributed over 23 countries. They show that leverage rates vary significantly across sectors, with the highest rates observed in transport and the lowest in water. Moreover, the authors also show that the 1997 Asia crisis led operators to adjust their financial structure differently in different regions. Overall, the evidence they present shows that debt is replacing equity in financing the investment needs of utilities and transport services in developing countries. These results raise some questions as to whether the regulator's mandate should be expanded to monitor the financial structure of companies and as to whether the international community should make a stronger commitment to more transparent regulatory accounting systems.